Effect of E-waste copper alloy additions on the microstructure and organization of Cu90PSn brazing joints - Bao, Li; Yang, Jiao; Zhang, Shannan; Ding, Tianran (Frontiers in Chemistry, 2024)
The effects of different contents of e-waste alloy on the microstructure and joint properties of Cu90PSn brazing filler metal was investigated during copper and copper brazing. Microstructure of base metal and brazing filler metal was studied with scanning electronic microscopy (SEM). The properties of brazing joint obtained by adding different electronic waste filler metal for smelting copper alloy were compared together. The results indicated that the fluidity of Cu90PSn brazing filler metal was weakened and the spreading property of Cu90PSn brazing filler metal was damaged after the addition of e-waste copper alloy. The structure of Cu90PSn brazing filler metal is mainly composed of (Cu), Cu3P and (Cu,Sn) compounds. When a small amount of electronic waste copper alloy is added, a trace amount of Fe in the brazing filler metal is distributed in the matrix structure of the filler metal in the form of solid solution. With the increase of copper alloys contents by smelting e-waste, Fe content in Cu90PSn brazing filler metal increases; the granular Fe3P phosphide changes into lamellar form. The Cu3P compound phase changes from continuous large orderly arrangement to discontinuous small block structure. Therefore, adding a trace amount of electronic waste copper alloy to the solder induction brazing copper/copper can obtain a uniform composition of the brazing structure. And the welding performance is not affected. However, As the content of e-waste smelted copper alloy continues to increase, the tensile strength shows a downward trend, which is attributed to the presence of brittle compound Fe3P in the joint.